The Impact of Graphene Oxide Nanoparticles Decorated with Silver Nanoparticles (GrO/AgNP) on the Cellulose Acetate (CA) Membrane Matrix Used for Hydrocarbon Removal from Water - Marian Băjan; Diana Luciana Cursaru; Sonia Mihai (Membranes)
Adding nanomaterials to polymer membranes can improve certain properties, such as the photocatalytic degradation of contaminants and antibacterial qualities. However, the interaction between nanomaterials and polymers is often limited by the presence of functional groups that can trap nanostructures within the polymer matrix. This study focuses on the synthesis of silver-decorated graphene oxide nanoparticles and their integration into cellulose acetate membranes. Characterization of the membranes was conducted using various techniques, including electron microscopy (SEM), thermogravimetric analysis, FTIR, goniometry, and filterability tests. The results indicate that CA membranes with decorated nanoparticles exhibit improved thermal stability, making them more effective for removing heavy hydrocarbons without the risk of nanomaterial elution during temperature fluctuations in the contaminated water flow subjected to filtration. Furthermore, these decorated structures enhance hydrophobicity due to interactions between the oxygenated groups of GrO and silver ions. While these additional networks may reduce the permeate flow rate, they significantly increase the efficiency of contaminant removal.